Inhibition of Quorum Sensing and Biofilm Formation of Esculetin on Aeromonas Hydrophila - Sun, Bing; Luo, Huaizhi; Jiang, Huan; Wang, Zhennan; Jia, Aiqun (Frontiers in Microbiology, 2021)
Quorum sensing (QS) and biofilm formation inhibition activity of esculetin on Aeromonas hydrophila SHAe 115 was evaluated. Exposure to esculetin at 25, 50, and 100 μg/mL signiﬁcantly inhibited the production of protease and hemolysin, the formation of bioﬁlms and attenuated the swarming motility of A. hydrophila SHAe 115. Biofilm forming inhibition was also observed through confocal laser scanning microscopy (CLSM) and scanning electron microscope (SEM). qRT-PCR analysis indicated that genes positively related to QS and biofilm formation were down-regulated to varying degrees, while gene (litR) negatively related to biofilm formation was significantly up-regulated. The phenotypic results were in good agreement with gene expression levels. These results indicated that esculetin would be a potential QS inhibitor for A. hydrophila.